Контроль изоляции сетей низкого напряжения методами двух и трех отсчетов вольтметра - Olszowiec, Piotr (НТУ "ХПИ", 2016)
Представлено применение методов контроля изоляции сетей низкого напряжения постоянного и двойного рода тока с помощью вольтметра и резистора. Приведены формулы для вычисления сопротивления изоляции методами двух и трех отсчетов вольтметра. Предложен новый способ двух отсчетов вольтметра для сетей двойного рода тока. Представлена модификация рассматриваемых методов, ограничивающая их основной недостаток – длительность переходного процесса.

Purpose. In the paper there are described methods of two and three voltmeter readouts for insulation resistance periodic measurement in live DC and AC/DC IT networks. A new measuring method for AC/DC networks is proposed. Application of a novel algorithm for shortening of measurement cycle is explained. Methodology. All methods of two and three voltmeter readouts consist in connection of a resistor and measurement of mean value of network’s fixed point-to-ground voltages. Results. A new algorithm implemented in KDZ-3 device enables determination of steady-state voltage of a DC network’s pole much faster than in other exploited systems. Originality. In author’s modification of two voltmeter readouts method, line-to-ground voltage mean value is measured at AC side of AC/DC network. This innovation has not been applied for implementation of periodic insulation monitoring in AC/DC IT networks yet. Practical value. The use of author’s innovation will allow to execute measurements at AC side of AC/DC IT networks which might be necessary if rectifier’s output circuits are unavailable. Shortening of measurement cycle duration of two or three voltmeter readouts method’s is of great importance in networks with high capacitance.
Low voltage networks insulation monitoring with two and three voltmeter readouts methods
Keywords: сети низкого напряжения постоянного тока; сопротивление изоляции; low voltage DC; AC/DC IT networks; insulation resistance